GENERAL FUNDAMENTAL RULES OF CIVIL PROCEDURE AND THEIR APPLICATION IN THE SEARCH FOR EFFECTIVE ENFORCEMENT MEASURES - Soares, Igor Clem Souza; Gomes, Marcos Paulo Pereira (Seven Editora, 2025)
This article aims to analyze the relationship between the fundamental rules of the process and executive protection. Executive protection refers to the effectiveness of judicial decisions and the implementation of the measures necessary to realize recognized rights. To understand this correlation, the principles, guarantees and procedural mechanisms related to the execution of judicial decisions are explored, such as the contradictory principle, cooperation, and the instruments used to carry out executive protection. Furthermore, the limits and possibilities of executive protection are discussed, considering the need to balance the effectiveness of execution with the protection of the debtor's rights. The article aims to provide a comprehensive understanding of the importance of reconciling the effectiveness of execution with respect for procedural principles and guarantees, aiming for a balanced and fair procedural system.DOI: https://doi.org/10.56238/sevened2025.017-004